Business, public policy, and society - Lesser, Lawrence M. (Thomson, 2006)
The book not only addresses timely theories and concepts related to ethics, social responsibility and public policy, but it adds relevance through real-life applications in business. It contains exclusive interviews in which corporate and trade association executives explain in their own words how they manage their responsibilities toward government and society. The text also explains how companies and industries use technology and telecommunications to promote and defend their public policy and societal interests in the U.S. and around the world. Thus, the text also has a strong global focus, containing international perspectives and examples. The text uses theories, concepts and historical developments to help students build a foundation and develop an analytical framework for the practical applications and policy discussions that follow. And it includes cutting-edge topics in business ethics and society--presented in a pro/con format--that have been classroom tested to increase student interest, promote class discussion, and enable students to develop their critical thinking skills